2020
DOI: 10.1371/journal.pone.0244210
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic classification of strain PO100/5 shows a broader geographic distribution and genetic markers of the recently described Corynebacterium silvaticum

Abstract: The bacterial strain PO100/5 was isolated from a skin abscess taken from a pig (Sus scrofa domesticus) in the Alentejo region of southern Portugal. It was identified as Corynebacterium pseudotuberculosis using biochemical tests, multiplex PCR and Pulsed Field Gel Electrophoresis. After genome sequencing and rpoB phylogeny, the strain was classified as C. ulcerans. To better understand the taxonomy of this strain and improve identification methods, we compared strain PO100/5 to other publicly available genomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…C. silvaticum is a new species comprising bacteria formerly described as untypical C. ulcerans strains isolated from roe deer and wild boars in Germany and Austria [ 50 ]. Later, a broader distribution of the species with strains isolated in Portugal was reported [ 51 ]. A phylogenetic analysis showed that the species has diverged into two clades.…”
Section: Relevance and Properties Of Toxigenic Corynebacteriamentioning
confidence: 99%
“…C. silvaticum is a new species comprising bacteria formerly described as untypical C. ulcerans strains isolated from roe deer and wild boars in Germany and Austria [ 50 ]. Later, a broader distribution of the species with strains isolated in Portugal was reported [ 51 ]. A phylogenetic analysis showed that the species has diverged into two clades.…”
Section: Relevance and Properties Of Toxigenic Corynebacteriamentioning
confidence: 99%
“…All the genomes were annotated in PATRIC using RASTtk (Brettin et al 2015). The taxonomy of the samples had previously been veri ed as C. ulcerans or C. silvaticum (Viana et al 2020) using FastANI (Jain et al 2018), and were additionally submitted to the Type Strain Genome Server (Meier-Kolthoff and Göker 2019) to con rm their taxonomy.…”
Section: Samplesmentioning
confidence: 99%
“…It is known so far that it is cytotoxic in humans (Möller et al 2021). Therefore, the bacterium has a zoonotic potential that leads to a potential economic loss in animal production (Dangel et al 2020;Viana et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations